Fetal growth restriction in a genetic model of sporadic Beckwith–Wiedemann syndrome - Simon J. Tunster; Mathew Van de Pette; Hugo D. J. Creeth; Louis Lefebvre; Rosalind M. John (Disease Models & Mechanisms, 2018)
Beckwith–Wiedemann syndrome (BWS) is a complex imprinting disorder involving fetal overgrowth and placentomegaly, and is associated with a variety of genetic and epigenetic mutations affecting the expression of imprinted genes on human chromosome 11p15.5. Most BWS cases are linked to loss of methylation at the imprint control region 2 (ICR2) within this domain, which in mice regulates the silencing of several maternally expressed imprinted genes. Modelling this disorder in mice is confounded by the unique embryonic requirement for Ascl2, which is imprinted in mice but not in humans. To overcome this issue, we generated a novel model combining a truncation of distal chromosome 7 allele (DelTel7) with transgenic rescue of Ascl2 expression. This novel model recapitulated placentomegaly associated with BWS, but did not lead to fetal overgrowth.